Analysis-oriented model for FRP tube-confined concrete: 3D interpretation of biaxial tube behaviour. (1st December 2022) - Li, Zhiyuan; Feng, Peng; Yang, Jia-Qi
Highlights: The nonlinear biaxial behaviours of filament-wound FRP tubes are interpreted with analysis-oriented model. The biaxial behaviour of filament-wound FRP tube is analysed based on the Classic Laminate Theory. Simplified design factors considering the nonlinear biaxial tube behaviours are proposed. Abstract: Filament-wound fibre-reinforced polymer (FRP) tubes are an emerging FRP product employed in various FRP-concrete composite structures, such as concrete-filled FRP tubes (CFFTs). Due to the fibre orientations in the tube wall, the filament-wound FRP tube exhibits biaxial behaviour under simultaneous axial compression and hoop expansion, causing relaxation of the confining stress. Therefore, the conventional hoop tension test may result in overestimation of the confining stiffness. In this paper, the biaxial behaviour of FRP tubes is theoretically investigated using classical laminate theory in conjunction with an analysis-oriented model for FRP-confined concrete. The geometrical meaning of the biaxial tube behaviour is interpreted intuitively using the 3D geometrical approach previously proposed by the authors. For the convenience of analysis and design, this paper proposes a simplified approach to rectify the confining stiffness that considers both elastic and nonlinear biaxial effects. The predicted results show good agreement with the collected test data.